Overview of some toxic plants for medicinal use: Case of the Central Middle Atlas – Morocco - Najem, Mariame; Bachiri, Lamia; Bouiamrine, El Houssine; Ibijbijen, Jamal; Nassiri, Laila (Ethnobotany Research and Applications, 2020)
Background: In Morocco, especially in the central Middle Atlas region, herbal medicines are an integral part of the lives of the inhabitants. However, the risks associated with this use remain underestimated. This is why the objective of this work is is to collect the maximum of information on the toxicological profile of certain medicinal plants of the traditional regional pharmacopoeia. Methods: The approach consists first of all in exploiting the data collected at the end of an ethnobotanical study carried out in the Central Middle Atlas, among certain practitioners of traditional medicine; indeed, they revealed the use of many plants recognized as toxic in the preparation of their medicinal recipes. Then, in a second stage, a synthesis work is done; it consists in collecting toxicological information published in specialized journals and books, on these toxic plants for medicinal use. Results: The survey led to the compilation of a list of 22 plants, selected on the basis of their declaration as toxic by 100% of the respondents. For its part, bibliographic research concerning these plants has confirmed their toxicity; it has also revealed that these plants can affect all the physiological functions of the body and sometimes cause irreversible damage that can be fatal. Furthermore, the comparison of the ethnobotanical use of the inventoried species with the information collected on their respective toxicological profiles has made it possible to see that in several cases, the toxic organ at the level of a given plant is itself that used for imprecise doses, in traditional medication. Conclusion: In the Central Middle Atlas region, many plants used for medicinal purposes are toxic; certainly, their therapeutic virtues are confirmed, but their toxicity requires constant vigilance. Keywords: Medicinal plant, Toxicity, Traditional medicine, Middle Atlas, Morocco.